Consumer demand for Community Supported Agriculture: a comparative study of the Kansas City (USA) and Midi-Pyrenees (France) regions - Baudouin, Quentin (Kansas State University, 2010)
Farmer-to-consumer direct marketing institutions have expanded significantly in the last decades. In particular, Community Supported Agriculture (CSA) has developed exponentially in the US and in Europe. CSAs consist of a contract in which the consumer buys a share of the farm production at the beginning of the season and receive in exchange a bundle of products regularly. CSAs still account for a marginal share of food sales today and many questions remain unanswered, such as the level of knowledge of the general public about CSA, the potential size of the market, its consumer characteristics, and the main motivations and barriers that lead consumers to either join or not join CSAs. This study focused on addressing these questions for the Kansas City area and the central region in France. Another objective was to give recommendations to farmers on how to develop CSAs. Two versions of the surveys were designed and conducted in the US and in France to address the objectives. Particularly, two types of questions were used in order to elicit willingness to pay (WTP): an open-ended question and a choice experiment. A Tobit model and discrete choice models were run to analyze results from the open-ended question and the choice experiment, respectively. Results show that around 80 percent of the population knew little about CSAs. The understanding of the demand for CSAs shows that a potential market, accounting for around 25 percent of the population, exists, but consumers are very exigent and farmers need to provide well-considered contracts to attract consumers. Recommendations to farmers are presented following the 4P method. For the Product, the variety offered seems to be the most important point. For Price, it has been estimated from the demand at $300 in the US and €400 in France for a basic share. Promotion would need to focus on education. Having various delivery locations would be the best option concerning Place; home delivery was found to be unnecessary. Tendencies found in the US and in France were similar except for educational activities: the French are looking more for these opportunities than Americans who care more about convenience.
Keywords: CSA; consumer demand; choice experiment; Economics, Agricultural (0503)